Digital Economy and Business Transformation in Indonesia: An Exploration of Opportunities and Challenges - Alfie Faj’ri, Fauziah; Amsal Sahban, Muhammad; Saragih, Hendra; Cyntia Kojongian, Patricia Jeaneth (PT. Anagata Sembagi Education, 2024)
This research explores the impact of the digital economy on key sectors such as e-commerce and fintech and identifies the challenges companies face in the adoption of digital technologies. In the context of e-commerce, this research assesses how digitalization has changed the way businesses operate, including changes in business models, payment methods, and customer experience, as well as how technology has enabled market expansion and improved operational efficiency. Using a qualitative approach and literature review, the research leveraged data from annual reports of government agencies, international organizations, industry reports of market research firms, and academic journal articles on digital transformation. The results reveal that, while digitalization offers significant opportunities for market expansion, innovation, and increased financial inclusion, there are serious challenges that include infrastructure limitations, digital skills gaps, and regulatory uncertainty. The implications of these findings point to the need for inclusive infrastructure development strategies, comprehensive skills training programs, and adaptive regulatory policies. Such measures are expected to address existing gaps and maximize the benefits of the digital economy for business growth as well as the national economy.